The soft skills bases in digital academic entrepreneurship in relation to digital transformation - Ana Garcez; Mário Franco; Ricardo Silva (Innovation & Management Review, 2023)
Purpose Digital technology changes the organizational structure of traditional firms, creating opportunities for entrepreneurship. These modifications are known as 'digital transformation' (DT). In addition, higher education institutions (HEIs) are altering the form of student-lecturer and teaching-learning interaction, where DT restructures the bases of soft skills (SS). Since SS are difficult to measure, this study aims to analyze the bases of SS for digital academic entrepreneurship, responding to the following research question: What are the bases of digital academic entrepreneurship and how are they formed? Design/methodology/approach An extensive integrative review of the literature revealed that due to the editable, re-combinable, reprogrammable and generating nature of digital technology, the basis of DT, it is necessary to develop SS in higher education students. Findings The results show that the competencies can be developed considering three major groupings: (1) individual characteristics, (2) cultural characteristics and (3) knowledge sharing. Practical implications Since SS are not easily taught, this study shows how the use of digital tools can help and support this type of process. It is suggested, therefore, that those in charge of HEIs should use the pillars presented in the framework proposed here to guide their institutions' strategic planning. With these pillars in mind, the aim is to stimulate an entrepreneurial mentality in students and develop digital academic entrepreneurship. Originality/value An innovative conceptual model of digital academic entrepreneurship is proposed from the perspective of SS, where the interlinking of those groupings is permeated by DT, as well as the disruptive role of digital technology, leading to the development of an entrepreneurial mentality in HEI students.
Keywords: 650; Digital academic entrepreneurship; Digital transformation; Entrepreneurial mindset; Soft skills